"From Linear To Circular": The transformation of fashion's supply chain into a value maximisation circular economy - Martins, Madalena Alves da Silva Crespo (2022)
"How can a product that needs to be sewn, grown, harvested, combed, spun, knitted, cut and stitched, finished, printed, labeled, packaged and transported cost a couple of euros?" (BoF, 2021). This was one of the questions raised by Li Edelkoort, in her 2015, Anti-Fashion Manifesto, when she anticipated the end of "Fashion as we know it". The conventional Linear system of the Fashion and Textiles Industry (FTI) is presented with a variety of environmental, social and economic issues that are becoming subjects of debate. In this study, the concept of Circular Economy is clarified and proposed as an integrated framework that can serve as a guideline that companies can follow in order for the transformation in the industry to happen. This included the categorisation of Circular Product Design Strategies, Circular Business Models and sub-models that were proposed as possible solutions to each stage of the FTI. The fieldwork comprised the development of a questionnaire, giving a general overview of what is already being applied by the Portuguese FTI companies, followed by a case study with an exemplary Portuguese company. This served as a starting point to see if the company influenced or not it supply and value chains to start implementing circular strategies as well. The results obtained indicate that the transition for a Circular Economy is fostered by several factors with legislation and political drive being fundamental for a transformation at scale, since, laws and regulations are fundamental to pursue education, investments and traceability.